AKIBAT HUKUM TERHADAP PELAKU USAHA YANG MELAKUKAN PENGOPLOSAN AIR MINUM DALAM KEMASAN YANG MENGAKIBATKAN KERUGIAN BAGI KONSUMEN DITINJAU UU NOMOR 5 TAHUN 1999 MENGENAI LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT DAN UU NOMOR 8 TAHUN 1999 MENGENAI PERLINDUNGAN KONSUMEN (KASUS PENGOPLOSAN AIR MINUM DALAM KEMASAN TAHUN 2017 ) - Hanna Margareth; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2021)
Community economic activities in particular are growing rapidly. Economic development covers several aspects of life in society , namely aspects of culture that are material in nature and rapidly changing and social changes in the economic field which include changes in society to meet various needs in life. One of the needs of people's lives that has an important role is the need for clean drinking water. Community life in the midst of busy activities that have taken up a lot of time and energy requires every individual to maintain good body health. Water is the largest body component and maintains the function of various organs of the human body. Adequate body fluids become very important to be maintained and noticed. Humans need quality drinking water, they need air that is safe for the body and humans are required to drink at least 2 liters of water a day. If there is a lack of water in a person's body, then humans will experience dehydration and lack of fluids in their bodies. Therefore, air has the most important role for humans to survive .